The proteolysis targeting chimera GMB-475 combined with dasatinib for the treatment of chronic myeloid leukemia with BCR::ABL1 mutants - Ye, Wu; Wu, Xia; Wang, Xiaojia; Wei, Xiaoyu; Tang, Yuqian; Ouyang, Xianfeng; Gong, Yuping (Frontiers in Pharmacology, 2022)
Patients with chronic myeloid leukemia (CML) show resistance to tyrosine kinase inhibitors (TKIs) targeting ABL1 due to the emergence of BCR::ABL1 mutants especially compound mutants during the treatment, which brings great challenges to clinical practice. Combination therapy is an effective strategy for drug resistance. GMB-475, a proteolysis targeting chimera (PROTAC) targeting the myristoyl pocket of ABL1 in an allosteric manner, degrades the BCR::ABL1 through the ubiquitin-proteasome pathway. In this study, we combined GMB-475 with orthosteric TKIs targeting ABL1 to overcome resistance. We constructed Ba/F3 cells carrying BCR::ABL1 mutants by gene cloning technology and compared the effects of combination therapy with those of monotherapy on the biological characteristics and signaling pathways in CML cells. We found that the effects of ABL1 inhibitors, including imatinib, dasatinib, ponatinib and ABL001, on growth inhibition and promoting apoptosis of Ba/F3 cells with BCR::ABL1 mutants especially compound mutants were weakened. GMB-475 combined with TKIs especially dasatinib synergistically inhibited growth, promoted apoptosis and blocked the cell cycle of Ba/F3 cells carrying BCR::ABL1 mutants and synergistically blocked multiple molecules in the JAK-STAT pathway. In conclusion, dasatinib enhanced the antitumour effect of GMB-475; that is, the combination of PROTAC targeting ABL1 in an allosteric manner and orthosteric TKIs, especially dasatinib provides a novel idea for the treatment of CML patients with BCR::ABL1 mutants in clinical practice.